DNA fragmentation of normal spermatozoa negatively impacts embryo quality and intracytoplasmic sperm injection outcome - Avendaño, Conrado (2010)
Objective: To evaluate DNA fragmentation in morphologically normal sperm recovered from the same sample used for intracytoplasmic sperm injection (ICSI) and to correlate DNA damage with embryo quality and pregnancy outcome. Design: Prospective study. Setting: Academic center. Patient(s): 36 infertile men participating in the ICSI program. Intervention(s): Terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate-fluorescein nick end labeling (TUNEL) assay and morphologic assessment by phase contrast. Main Outcome Measure(s): Simultaneous assessment of sperm morphology and DNA fragmentation by TUNEL assay was performed in the same cell, then the percentage of normal sperm with fragmented DNA (normal SFD) was correlated with embryo quality and pregnancy outcomes. Result(s): A highly statistically significant negative correlation was found between the percentage of normal SFD and embryo quality. This association was confirmed for the transferred embryos and for the total embryo cohort. The receiver operating characteristics curve analysis demonstrated that the percentage of normal SFD and embryo quality were statistically significant predictors of pregnancy. When the percentage of normal SFD was ≤17.6 %, the likelihood of pregnancy was 3.5 times higher. No correlation was found between the percentage of total sperm with fragmented DNA (morphologically normal and abnormal) and ICSI outcomes. Conclusion(s): The DNA fragmentation of morphologically normal sperm negatively impacts embryo quality and probability of pregnancy in ICSI cycles.